2003
DOI: 10.1097/01.wcb.0000090506.76664.00
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Model of Oxygen Delivery and Metabolism for Physiologic Interpretation of Quantitative Cerebral Blood Flow and Metabolic Rate of Oxygen

Abstract: Summary:The coupling of cerebral blood flow (CBF) and metabolic rate of oxygen (CMRO 2 ) during physiologic and pathophysiologic conditions remains the subject of debate. In the present study, we have developed a theoretical model for oxygen delivery and metabolism, which describes the diffusion of oxygen at the capillary-tissue interface and the nonlinear nature of hemoglobin (Hb) affinity to oxygen, allowing a variation in simple-capillary oxygen diffusibility, termed "effective oxygen diffusibility (EOD)." … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
99
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(99 citation statements)
references
References 40 publications
0
99
0
Order By: Relevance
“…In fact, Hattori et al (2004) recently showed that OEF values in three-step method were not identical to those in gOEF AÀV in human, suggesting the presence of physiologic change during the measurement. The present method may also make physiologic interpretations of flow and metabolism more accurate (Hayashi et al, 2003). Finally, it allows evaluation of coupling or uncoupling of CBF and CMRO 2 during functional activation or pharmacological stress, such as that induced by acetazolamide used for assessment of cerebral vascular reserves.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, Hattori et al (2004) recently showed that OEF values in three-step method were not identical to those in gOEF AÀV in human, suggesting the presence of physiologic change during the measurement. The present method may also make physiologic interpretations of flow and metabolism more accurate (Hayashi et al, 2003). Finally, it allows evaluation of coupling or uncoupling of CBF and CMRO 2 during functional activation or pharmacological stress, such as that induced by acetazolamide used for assessment of cerebral vascular reserves.…”
Section: Discussionmentioning
confidence: 97%
“…A deeper question is to ask why n is not equal to 1, because this is the central phenomenon underlying the BOLD effect. This is an area of active research (Aubert and Costalat, 2002;Buxton, 2004;Buxton and Frank, 1997;Gjedde et al, 1991Gjedde et al, , 2002Hayashi et al, 2003;Hyder et al, 1998;Woo and Hathout, 2001;Zheng et al, 2002), and as this work is refined it can be included as a central step in modeling the path from stimulus to BOLD response.…”
Section: Modeling the Hemodynamic Responsementioning
confidence: 99%
“…To achieve the ultimate goal of reconstructing neuronal activity from the haemodynamic responses measured, for example, via the fMRI signals (Buxton et al, 2004), it appears that current haemodynamic models have yet to be made more realistic physiologically (Hayashi et al, 2003;Fantini, 2002). For instance, usually only one vascular compartment is modeled, neglecting the fact that arteries, arterioles, capillaries, venules, and veins all have different responses.…”
Section: Implications For Modeling Cerebral Haemodynamics and Oxygen mentioning
confidence: 99%